Molecular Study for Respiratory Syncytial Virus in Thi-Qar Province, Iraq - Sally Salih Jumma; Basim adul Hussein Jarullah (مجلة علوم ذي قار, 2022)
Human respiratory syncytial virus (HRSV) is an important cause of acute respiratory infection (ARI) and mortality in humans; especially among children, elders and immune-compromised individuals around the world. This study aims to determine the infection rate of respiratory syncytial virus in patients with respiratory tract infection and identify the genotyping in Different cities in Thi-Qar province During the period from February to May. A total of 100 throat swabs samples were collected from patients having flu-like illnesses from age range between (6-65 ) years from both sex . Result showed 38 % positive for RSV , 24% was in genotype A and 14% in genotype B ,.The conclusion of this study revealed that respiratory syncytial virus A infections were more frequent than RSV B among patients with acute respiratory tract infection, and The frequency of female patients infected with RSV were higher than their male.